2017
DOI: 10.12659/msm.901191
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Genes Affecting Results of Hyperthermia in Osteosarcoma Based on Integrative ChIP-Seq/TargetScan Analysis

Abstract: BackgroundThe purpose of this study was to research the effects of hyperthermia on osteosarcoma (OS) by integrating the Chromatin Immunoprecipitation with the generation sequencing (ChIP-Seq) and TargetScan analysis of heat shock transcription factor 1 (HSF1).Material/MethodsThe HSF1 ChIP-seq dataset of GSE60984 was downloaded from the Gene Expressed Omnibus (GEO) database. The HSF1-binding sites were screened by MACS2 in OS cells after 10 and 20 min of hyperthermia, and they were annotated using the ChIPseeke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…Shortlisted circRNA-interacting miRNAs were further analyzed by mirPath v.3 (Vlachos et al, 2015) and TargetScan (Shi et al, 2017), leading to the discovery of pathways that may be mediated by circRNA-miRNA interactions. Pathway/category union was predicted by mirPath v.3 (Vlachos et al, 2015) and TargetScan (Shi et al, 2017), which identified all the pathways significantly targeted by the selected microRNAs. Fisher's meta-analysis method was used to calculate the significance levels and extract the merged p-values for each pathway.…”
Section: Pathway Analysis Of the Circrna-mirna Targeted Genesmentioning
confidence: 99%
“…Shortlisted circRNA-interacting miRNAs were further analyzed by mirPath v.3 (Vlachos et al, 2015) and TargetScan (Shi et al, 2017), leading to the discovery of pathways that may be mediated by circRNA-miRNA interactions. Pathway/category union was predicted by mirPath v.3 (Vlachos et al, 2015) and TargetScan (Shi et al, 2017), which identified all the pathways significantly targeted by the selected microRNAs. Fisher's meta-analysis method was used to calculate the significance levels and extract the merged p-values for each pathway.…”
Section: Pathway Analysis Of the Circrna-mirna Targeted Genesmentioning
confidence: 99%
“…miRanda was used to match the entire miRNA sequences. The TargetScan (Shi et al, 2017) parameters were set as a context score percentile >50. The miRanda parameters (John et al, 2004) were set as free energy <−10 kcal/mol and a score >50.…”
Section: Bioinformatics Analysis Of Mrna and Mirna Transcriptome Datamentioning
confidence: 99%
“…The target genes of miRNA-146a-5p were predicted by Targetscan [10] (http://www.targetscan.org/vert_72/), miRDB [11] (http://mirdb.org/), miRWalk [12] (http://zmf.umm.uniheidelberg.de/apps/zmf/mirwalk/), and PicTar [13] (https://pictar.mdc-berlin.de/), the results were admitted into draw Venn diagram [14] and the results belonged to the 4 databases were selected. Then we get the sequence of miRNA-146a-5p and the target gene and look for the combining site to identify the relationship between them.…”
Section: Bioinformatics Analysismentioning
confidence: 99%